The internationalization of social hybrid firms - Angulo-Ruiz, Fernando; Pergelova, Albena; Dana, Leo-Paul (My University, 2020)
This paper is concerned with the internationalization of firms that combine social and profit objectives at their core, referred to as social hybrid firms. In contrast to most profit-focused firms, such firms tend to place considerable attention on the social impact within their local communities. For this reason, the internationalization behavior of these firms has received limited research attention. In our empirical setting, however, some social hybrid firms go beyond their local communities and internationalize. Using the attention-based view as a theoretical framework, we hypothesize several boundary conditions that affect the internationalization of social hybrid firms and test them with a representative data set of small and medium-sized, privately-owned, indigenous businesses in Canada. Our findings reveal that social hybrid firms are more likely to internationalize when the levels of institutional isomorphism are high and when the organization leverages economic network ties. However, social network ties and government support reduce the likelihood of social hybrid firms to internationalize. The study provides theoretical and practical implications related to the phenomenon of social hybrid firms, their internationalization, and the attention-based view of the firm.
Keywords: social hybrid firms; internationalization; attention-based view; networks; government support; institutional isomorphism; Indigenous business